Combined modality treatment with organ preservation in invasive bladder cancer - Čufer, Tanja (Radiology and oncology (Ljubljana), 2000)
Background. The standard treatment for muscle-invasive bladder cancer is stillradical cystectomy. However despite mutilating surgery half of the patients eventually develop metastatic disease and subsequently die of the disease. In view of these problems, a bladder-sparing approach using multi-modality treatment with transurethral resection (TUR), irradiation and chemotherapy has been tested in this disease. So far, the results published byfive groups, showed that the survival rates of patients treated by multi-modality therapy with a bladder sparing approach, based on the response to initial TUR and chemotherapy or chemoradiotherapy, are comparable to cystectomy series, while also offering a 60% to 70% chance of maintaining a functioning bladder. The probability of survival with bladder preserved was found to be around 40% at 5-years. The best predictor of successful multi-modality treatment with bladder preservation seems to be a complete response to initial therapy and a close cystoscopic surveillance is obligatoryto allow for cystectomy at earliest opportunity, if necessary. Conclusions. Multimodality treatment with selective bladder preservation offers a chance for long term cure and survival equal to radical cystectomy inmuscle invasive bladder cancer, while also offering a chance of maintaining a normally functioning bladder. It is expected, that the identification of biological factors with a predictive value for successful chemoradiation will allow for a better selection of patients who could benefit from this treatmentin future.
Keywords: Bladder neoplasms; Combined modality therapy; Cystectomy; Drug therapy; Methods; operativno zdravljenje; Radiotherapy; rak (medicina); sečni mehur; Surgery; Survival analysis; zdravljenje